2007
DOI: 10.1108/13620430710724811
|View full text |Cite
|
Sign up to set email alerts
|

Exploring career‐life success and family social support of successful women in Canada, Argentina and Mexico

Abstract: PurposeThe purpose of this paper is to examine career‐life issues of successful women in the Americas.Design/methodology/approachA total of 30 interviews were conducted with successful women in Canada, Argentina and Mexico. Themes were pulled from the interview transcripts for each country, analyzed and then compared across countries, looking at universalities and differences of experiences.FindingsThe women in all three countries conveyed more subjective measures of career success, such as contributing to soc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
61
1
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(67 citation statements)
references
References 29 publications
4
61
1
1
Order By: Relevance
“…Women define their career differently than do men. Their definitions of success often focus on subjective rather than just objective outcomes (Lirio et al, 2007;Sturges, 1999;Pachilicz et al, 2008;Valcour and Ladge, 2008;Wise and Millward, 2005). In protean careers, career success is internal, based on fulfillment of one's personal values.…”
Section: Protean Careersmentioning
confidence: 99%
“…Women define their career differently than do men. Their definitions of success often focus on subjective rather than just objective outcomes (Lirio et al, 2007;Sturges, 1999;Pachilicz et al, 2008;Valcour and Ladge, 2008;Wise and Millward, 2005). In protean careers, career success is internal, based on fulfillment of one's personal values.…”
Section: Protean Careersmentioning
confidence: 99%
“…Women may go through numerous cycles as they seek to create careers that satisfy their own personal needs and definition of success (Valcour and Ladge, 2008). As opposed to men, women's definitions of career success often focus on subjective rather than just objective outcomes (Lirio et al, 2007;Sturges, 1999;Pachilicz et al, 2008;Valcour and Ladge, 2008;Wise and Millward, 2005), because they generally have more non-work responsibilities than men, making it difficult to adhere to the norms of the traditional career model. In protean careers, career success is internal, based on one's personal values.…”
Section: The Protean Careermentioning
confidence: 99%
“…In the literature on career success, in contrast to men whose career aspirations are characterized by 'objective' factors like hierarchical advancement and remuneration, women's goals are described in terms of values such as personal accomplishment, interesting work and recognition (Sturges, 1999;Lirio et al 2007). Taking issue with this largely Western literature, studies have shown how South Asian women prioritize hierarchical advancement (Authors, 2011;Budhwar et al 2005) and financial security (Author B et al 2009).…”
Section: Women's Careers Aspirationsmentioning
confidence: 99%